L’arbre urbain : métissage et créolité à Tamatave (Madagascar) - Jean-Baptiste Bing (Projets de Paysage)
The second-largest agglomeration and first port of Madagascar, Toamasina, owes its position as the interface between the island and the outside world to its cross-cultural background. This article investigates the place occupied by and the uses made of trees in this mixed urban landscape. Based on two years spent in the city comparing methods (guided tours, urban strolls, formal and informal interviews and participative observations) the article investigates three areas in the city (Tanamakoa, Analakinina and the city centre). The first part of the article presents the theoretical and historical background revealing the links between the urban landscape of Toamasina and the mixed Creole identity of the city; the second examines the plural nature of the functions of the tree in this landscape, relating these to the different territorial dimensions expressed through the trees, and finally outlines further aspects for consideration regarding the pluridisciplinary nature of the urban landscape, its management and its evolutions.